Co-Active Leadership, Second Edition, 2nd Edition - Kimsey-House, Karen; Kimsey-House, Henry (Berrett-Koehler Publishers, 2021)
As leaders, how we are is as important as what we do. The second edition of a leadership classic, updated with new chapters, shows how to master the inner and outer work needed to build relationships that unleash the transformational creative potential in everyone. Top-down, one-dimensional leadership models are hopelessly outmoded in today's rapidly changing world. And they waste the leadership ability present throughout an organization, not just at the top. In the second edition of this visionary book, Karen and Henry Kimsey-House provide a model that harnesses the possibility of many rather than relying on the power of one. This new edition is updated with two additional chapters, one offering new ways to utilize the Co-Active Leadership Model and another that goes deeply into the Co-Active philosophy that drives the authors' approach. Each of the five dimension chapters is expanded to incorporate feedback, new language, case studies, and practical suggestions for practice and development. Co-active leadership is a deeply collaborative approach, but the last of its five dimensions focuses on the individual: leading from within. We must be fully present and live with integrity, openheartedness, and self-awareness if we are to make the kind of conscious, creative choices co-active leadership demands.